2020
DOI: 10.1177/0731684420962577
|View full text |Cite
|
Sign up to set email alerts
|

Analytical modeling for offshore composite rubber hose with spiral stiffeners under internal pressure

Abstract: Internal pressure is the most important functional load for the offshore composite rubber hose. In this paper, the stress and radial displacement of the hose under internal pressure are investigated. The hose dimensions are length of 10.7 m and nominal bore diameter of 500 mm. The composite structure is mainly composed of cord-rubber reinforcement layers and a spiral steel stiffener. To calculate the stress and deformation of the hose, the stiffener and composite cord-rubber layers are theoretically analyzed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 20 publications
(34 reference statements)
0
14
0
Order By: Relevance
“…A detailed crush load effect is recommended to investigate the effect of couplings and end-fittings of marine hoses when in contact with the FPSO body or reeling drum. Typical nonlinear analyses of spring models with similar failure mode analysis of hoses are in [48][49][50][51]82].…”
Section: Results Of Crush Load On Helix Springmentioning
confidence: 99%
See 1 more Smart Citation
“…A detailed crush load effect is recommended to investigate the effect of couplings and end-fittings of marine hoses when in contact with the FPSO body or reeling drum. Typical nonlinear analyses of spring models with similar failure mode analysis of hoses are in [48][49][50][51]82].…”
Section: Results Of Crush Load On Helix Springmentioning
confidence: 99%
“…Secondly, these multi-layered risers have similar behaviour to marine hoses in mechanical performance. They both exhibit some mechanical-related behaviours in terms of delamination, contacts, liner collapse, and fatigue [46][47][48][49][50][51]. In principle, these marine hoses are designed using both global and local designs [52][53][54][55].…”
Section: Introductionmentioning
confidence: 99%
“…Different studies have been conducted on the numerical modelling of hose-mooring systems for marine hoses [46][47][48][49][50][51][52][53][54][55][56], CALM buoys [57][58][59][60][61][62][63][64][65][66][67], and offloading systems [68][69][70][71][72][73][74][75][76][77][78]. Most studies on marine hoses does not include mooring line safety ([36,37,42-45,79-88]).…”
Section: Safety Precautions At Spm Mooring Terminalsmentioning
confidence: 99%
“…The results showed that the appropriate mixing process can improve the dispersion of silica in the rubber matrix, and the rubber can be degraded when the rotor speed reaches 60 rpm. Gao et al 15 studied the structure of rubber hoses and observed that the reinforcing ribs have an important influence on the mechanical properties of rubber composite materials. Under an external stress, the reinforcing ribs may result in a greater strength of the rubber hose.…”
Section: Introductionmentioning
confidence: 99%